(3ebOeI aj CSGSjGJ eMGSHI GdJcGdjas - (3eQYj(B, (3YHO GdMjs ((3GdEScfOQjI(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2006)
(3JLO aj gPG GdcJGH (B: (3CgOGa eMGSHI GdJcGdja aj GdeGVj hGdMGVQ hGdeSJbHd , eaGgje GdJcdaI hYfGUQgG , fXe bjGS JcdaI GdEfJGL ,eONd bjGS GdJcdaI , JSLjd YfGUQ GdJcGdja , GdeMGSHI Yf GdJcdaI GdUfGYjI ZjQ GdeHGTQI hGdQbGHI YdjgG GdQbGHI Ydi GdehGQO hGdNGeGJs
Keywords: (3eMGSHI GdJcGdjas